Peran Guru dalam Pendidikan Multikultural pada Pengembangan Nilai Empati Siswa - Irma Sari Daulay; Indah Kurnia Hasibuan; Siti Khadijah Hasibuan; Maya Sari Hasibuan; Ulfa Fadhilah Lubis; Hotma Dewita Siregar; Siti Latifah Zulkaedah (JURNAL ILMIAH RESEARCH STUDENT, 2026)
Multicultural education is an important approach to instilling empathy in the midst of Indonesia’s diverse society. Teachers play a strategic role as agents of change in shaping students’ character to live harmoniously alongside various backgrounds. This study aims to describe the role of teachers in developing students’ empathy through multicultural education at Madrasah Ibtidaiyah in Padang Lawas Regency. The research employs a qualitative approach with a descriptive method, and data collection techniques include observation, in-depth interviews, and documentation. The findings reveal that teachers are aware of the importance of diversity as part of the educational process and integrate empathy values into learning through strategies such as cross-background group discussions, the use of folklore, and reflective activities. Teachers also serve as role models in inclusive and fair attitudes toward all students. The success of teachers is supported by an open school environment, madrasah policy support, and personal commitment, although obstacles such as limited training and time constraints remain. This study concludes that the role of teachers is crucial in fostering student empathy through continuous multicultural education.